Effect of temperature on current pulse characteristics of negative corona discharge based on numerical model - Zhang, Lijing (2023)
Temperature is an important factor affecting the dynamic processes of corona discharge, since the ionization, attachment, and mobility of charged particles are directly related to temperature. Most existing research has investigated the temperature effect on corona discharge through experimental works. However, they are hard to acquire the corona discharge microphysical processes, which are related to the formation of the current pulse and electromagnetic (EM) wave signals. This article proposes a numerical model with temperature-related transport parameters to study the temperature influence on microphysical processes and current pulses for negative corona. By comparing microphysical quantities such as the effective ionization coefficient, density, and velocity of space charges, the effect of temperature on the current pulse parameters including the rise and fall times, amplitude, and pulsewidth is systematically explained. It shows that as the temperature rises, the current pulse amplitude increases, while the other three parameters decrease. The rise time is dependent on the effective ionization coefficient. The fall time is affected by the velocities of negative and positive ions. The experimental results indicate the simulated current pulses are consistent with the measured ones, proving the effectiveness of the proposed numerical model with temperature variation.